Semiotic Analysis in Skintific Indonesia Products Advertisements - Sipahutar, Ike Nurmayanti; Manik, Sondang; Pasaribu, Arsen Nahum (SOCIETIES: Journal of Social Sciences and Humanities, 2024)
Abstract. Semiotics is the study of how a sign or symbol is used to produce meaning. This research aims to describe the denotation meaning, connotation meaning, and myth contained in the advertisement of Skintific Indonesia products. The analysis uses Barthes' theory. This research focuses on the exploration of visual and verbal elements in advertisements. The research method uses a qualitative descriptive method. Data was taken from the Youtube platform. The results showed that Skintific Indonesia advertisements have visual signs and verbal signs. In the denotation meaning, there are elements such as product, model, color, and text that explicitly describe the product as brightening, anti-acne, moisturizing, and others. In the connotation meaning, there are visual designs that are explicitly meaningful to give an impression of the product and also provide benefits from the manufacturer. In this research, no myths were found. Skintific products are considered an important part of achieving grooming style. In this way the author uses Barthes' theory, revealing the meanings hidden in the visual and verbal used in the advertisement. It can be understood how the Skintific Indonesia brand can attract the attention of wider community and how the advertisement uses verbal/words used to explain products associated with certain values such as natural beauty, long-lasting, healthy, and has no side effects in its use. This research also reveals important meanings hidden in Skintific Indonesia product advertisements and how semiotic elements can be used to create a positive relationship between brands and consumers. Keywords: Semiotic; Denotative; Connotative; Myth; Products advertisements.